A modified GAC model for extracting waterline from remotely sensed imagery. Issue 17 (1st September 2016) - Ruan, Kun; Zha, Yong; Zhou, Zeming; Yang, Pinglv
ABSTRACT: At present many methods are available for extracting waterline automatically from remotely sensed imagery. They are commonly limited by their inability to accurately detect waterline when the land–sea interface is not so distinctive on the imagery. This study aims to develop a new model of extraction in which both the spectral features of water and the spatial feature of waterline itself are incorporated into the level set framework. This model consists of three terms. The first term, which is derived from the spectral features, drives the curve evolution. The second term, curvature flow, guarantees the smoothness of the curve in the process of evolution. The third term, the boundary attraction force, attracts the evolving curve to the genuine position. Experimental results with Landsat Thematic Mapper (TM) data sets validate the effectiveness of the proposed model. It can improve the accuracy of extracted waterline and effectively prevent the omission of weak boundaries from the detected results that are common in both geodesic active contour (GAC) and distance-regularized level set evolution (DRLSE) results.